This weekend doesn't end well for anyone : a novel - Mack, Catherine (Mack, Catherine. Vacation mysteries, 2026)
In this third installment of the mystery series featuring author-turned-sleuth Eleanor Dash, a planned speaking engagement at a writers' conference in the Bahamas is disrupted when she discovers a body in her hotel room. Surrounded by fellow authors, acquaintances, and rivals--any of whom could be connected to the crime--Eleanor becomes involved in another investigation despite her attempts to take a vacation. The novel blends humor and suspense as Eleanor navigates personal relationships, professional tensions, and the challenges of solving a murder within a community of mystery writers.